Implementation of the quality family village program in East Ogan Komering Ulu regency: A qualitative study - Nanik Lestari; Nani Sari Murni; Muhammad Prima Cakra Randana (Lentera Perawat, 2025)
Background: The Quality Family Village Program (Kampung KB) is a strategic initiative of the Indonesian government aimed at improving family welfare at the village level through the integration of population, family planning, and family development programs. However, in East Ogan Komering Ulu (OKU) Regency, the program faces several challenges, including limited resources, suboptimal sustainability, and inconsistent implementation across administrative levels. Objective: This study aimed to explore the implementation of the Kampung KB program in Kerujon Village, Semendawai Suku III District, East OKU Regency in 2025. Methods: A qualitative case study design was employed. Data were collected through in-depth interviews, field observations, and document review involving 16 informants representing village, sub-district, and district stakeholders. Data were analyzed using the Miles and Huberman interactive model, which includes data reduction, data display, and conclusion drawing/verification. Results: Four major themes were identified: (1) communication, (2) resources, (3) implementer disposition, and (4) bureaucratic structure. Although implementers demonstrated strong commitment to the program, several barriers persisted, such as ineffective communication flow between administrative levels, inadequate human and material resources, weak intersectoral coordination, and low community participation. These issues hinder program optimization at the local level. Conclusion: The implementation of the Kampung KB program in Kerujon Village has progressed but remains suboptimal due to communication barriers, resource constraints, and limited organizational support. Strengthening strategic communication, enhancing resource capacity, and improving bureaucratic responsiveness are essential to advance program effectiveness. Local government should prioritize cadre training, establish structured communication mechanisms across levels, and increase community engagement in all phases of program planning, implementation, and evaluation.